Use of smartphone as ICT literacy media and learning resources among college students - Al Halim Ali Sunan; Ananda Julia Yasmin; Kholid Abdullah Harras (Inovasi Kurikulum, 2023)
This study aims to determine the extent to which students can use smartphones as ICT literacy media and learning resources. This is due to the development of increasingly advanced technology that requires the nation's generation to be able to face the challenges of the era, one of which is being able to use technologies, especially smartphones, for positive things, particularly in ICT literacy and as learning resources. The method used in this research is a descriptive method with a qualitative approach. The results of the study show that smartphones can be used as ICT literacy media and learning resources for college students. Also, students have been able to carry out ICT literacy well as evidenced by the use of existing applications on smartphones to search, obtain, and manage information, which later on this information can also be a source of learning. On the other hand, from the use of smartphones as learning and literacy media, there are also negative impacts, such as addiction and dependence on smartphones, the amount of negative content and fake news that can be found online. The solution that can be used to overcome this is the presence of self-control tools or high self-awareness from the students themselves. AbstrakPenelitian ini bertujuan untuk mengetahui sejauh mana mahasiswa dapat menggunakan smartphone sebagai media literasi TIK dan sumber belajar. Hal ini dikarenakan perkembangan teknologi yang semakin maju menuntut para generasi bangsa untuk dapat menghadapi tantangan zaman, salah satunya adalah mampu menggunakan teknologi, khususnya smartphone untuk hal yang positif, utamanya dalam literasi TIK dan belajar. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa smartphone dapat dijadikan sebagai media literasi TIK dan sumber belajar di kalangan mahasiswa. Selain itu, mahasiswa juga telah mampu melakukan literasi TIK dengan baik yang dibuktikan dengan penggunan aplikasi yang ada pada smartphone untuk mencari, mendapat, dan mengelola informasi, yang nantinya informasi tersebut dapat juga menjadi sumber belajar. Namun, dari penggunaan smartphone sebagai media belajar dan literasi tersebut, terdapat pula dampak negatif yang ditimbulkan, seperti kecanduan dan ketergantungan terhadap smartphone, banyaknya konten negatif yang ditemukan, serta banyaknya berita hoaks. Solusi yang dapat digunakan untuk mengatasi hal tersebut adalah adanya kontrol diri atau kesadaran diri yang tinggi dari mahasiswa itu sendiri.Kata Kunci: Literasi TIK; mahasiswa; smartphone; sumber belajar